Democracy, rationality and morality - Dennis C. Mueller (Max Planck Institute of Economics, 2006)
The fundamental, underlying assumption in economics, public choice, and increasingly in political science and other branches of the social sciences is that individuals are rational actors. Many people have questioned the realism of this assumption, however, and considerable experimental evidence seems to refute it. This paper builds on recent findings from the field of evolutionary psychology to discuss the evolution of rational behavior in humans. It then goes on to relate this evolutionary process to the evolution of political institutions and in particular of democratic institutions.
Keywords: 330